2018
DOI: 10.1253/circj.cj-17-0650
|View full text |Cite
|
Sign up to set email alerts
|

Third and Fourth Heart Sounds and Myocardial Fibrosis in Hypertrophic Cardiomyopathy

Abstract: Methods Study PopulationThe present retrospective study was performed on 53 consecutive patients with HCM (mean age 66 years; range 37-91 years) who underwent an initial assessment, including phonocardiography, echocardiography, LGE-MRI, and biomarker measurements, in Matsushita Memorial Hospital. All patients were clinically stable without symptoms of heart failure, such as dyspnea, fatigue, and edema. Although these initial examinations were not necessarily performed on the same day, there were no patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…A phonocardiogram was obtained at the apex as well as at the right and left sternal borders in the half left lateral decubitus position or supine position at a paper speed of 50 or 100 mm/s using a commercially available device (MES‐1000, Fukuda‐Denshi Co., Tokyo, Japan) (Honda et al, 2016 ; Sato et al, 2018 ), as shown in Figure 1 . Measurements included four frequencies: a low frequency, lower‐middle frequency, higher‐middle frequency, and high frequency.…”
Section: Phonocardiographymentioning
confidence: 99%
See 3 more Smart Citations
“…A phonocardiogram was obtained at the apex as well as at the right and left sternal borders in the half left lateral decubitus position or supine position at a paper speed of 50 or 100 mm/s using a commercially available device (MES‐1000, Fukuda‐Denshi Co., Tokyo, Japan) (Honda et al, 2016 ; Sato et al, 2018 ), as shown in Figure 1 . Measurements included four frequencies: a low frequency, lower‐middle frequency, higher‐middle frequency, and high frequency.…”
Section: Phonocardiographymentioning
confidence: 99%
“…S4 was considered to be present when a low frequency sound was recorded best at the apex between the onsets of the P wave and QRS complex of an electrocardiogram, coinciding with a large peaked A wave in an apexcardiogram if available (Tavel, 1971 ). S4 needed an amplitude of 1.0 mm or greater on the phonocardiogram with the above‐described settings (Sato et al, 2018 ). The presence or absence of S4 was assessed by two experienced cardiologists; disagreement was resolved by consensus.…”
Section: Phonocardiographymentioning
confidence: 99%
See 2 more Smart Citations
“…Определение III тона для выявления очагов накопления контрастного препарата характеризо-валось высокой специфичностью (97%), но низкой чув-ствительностью (29%) [24].…”
unclassified